Saint-Denys Garneau, écrivain et ethnographe : du Journal au Conte - Guilbert, Lucille (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1984)
AbstractThe very profitable relationship that exists between Saint-Denys Garneau's poetry and European literature has been thoroughly demonstrated. As a counterweight to this "learned" culture, Saint-Denys Garneau thrived on the oral tradition, particularly during his frequent stays in Sainte-Catherine and during his fishing trips with his uncle to Lac Jacques-Cartier. In his Journal and Correspondance, Saint-Denys Garneau noted observations, best described as ethnographical, on the everyday life of ordinary people, their customs, beliefs and stories. The ethnographical observations and descriptions that he noted in his Journal would serve as a basis for his Contes and Nouvelles. This article deals with the various transformations that oral stories underwent as they were re-fashioned into literary creations.